2014
DOI: 10.1007/s12032-014-0227-x
|View full text |Cite
|
Sign up to set email alerts
|

Cullin1 regulates proliferation, migration and invasion of glioma cells

Abstract: This study was designed to explore the role of Cullin1 (Cul1) in the pathogenesis of human glioma and to investigate the role of Cul1 in the growth, migration and invasion of glioma cells. Expression of Cul1 in 191 glioma tissues, 8 normal brain tissues and 8 tumor adjacent normal brain tissues was analyzed by tissue microarray and immunohistochemistry. Cul1 expression in human glioblastoma cells was knocked down by specific siRNA to study the effect of down-regulation of Cul1 on proliferation, invasion and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…These might suggest that in addition to Pyk2 other pathways may be involved in the regulation of basal rates of migration in gliomas such as Insulin-like growth factor binding protein 3 (IGFBP-3) that has been implicated in the pathogenesis of gliomas and was shown to be involved in proliferation and the invasive capacity of glioma cells [ 53 ]. Other studies demonstrated that Culllin1 (Cul1) is increased significantly in malignant brain tumors, and that silencing of Cul1 in glioma cells inhibited the cell migration and invasion abilities as well as down-regulated MMP-2 and MMP-9 expression that also greatly contribute to the reduced cell invasion and migration abilities [ 54 ]. Golgi phosphoprotein 3 (GOLPH3) is also found to be upregulated in gliomas and involved in glioma cell migration and invasion via the mammalian target of rapamycin (mTOR)-Y-box binding protein-1 (YB1) pathway [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…These might suggest that in addition to Pyk2 other pathways may be involved in the regulation of basal rates of migration in gliomas such as Insulin-like growth factor binding protein 3 (IGFBP-3) that has been implicated in the pathogenesis of gliomas and was shown to be involved in proliferation and the invasive capacity of glioma cells [ 53 ]. Other studies demonstrated that Culllin1 (Cul1) is increased significantly in malignant brain tumors, and that silencing of Cul1 in glioma cells inhibited the cell migration and invasion abilities as well as down-regulated MMP-2 and MMP-9 expression that also greatly contribute to the reduced cell invasion and migration abilities [ 54 ]. Golgi phosphoprotein 3 (GOLPH3) is also found to be upregulated in gliomas and involved in glioma cell migration and invasion via the mammalian target of rapamycin (mTOR)-Y-box binding protein-1 (YB1) pathway [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five articles containing the key words were included in this systematic review. Three, two, and three clinical trials were encountered, respectively, when the keywords were entered as "glioblastoma and/or post transcriptional gene silencing" (3,7,43), "glioblastoma and/or small interfering RNA" (41,43), or "glioblastoma and/or siRNA" (7,22,40). After a full text review, the distribution of studies by years was presented (Table II).…”
Section: █ Resultsmentioning
confidence: 99%
“…They found that the survival time at 18 months was 62% for patients testing positive for a methylated MGMT promoter and suggested that long-term survival could be achieved by silencing the MGMT gene by promoter methylation (13). In conclusion, after evaluating the data obtained from our literature review, only five studies containing all our search criteria were found (3,7,22,40,43).…”
Section: █ Conclusionmentioning
confidence: 93%
See 1 more Smart Citation
“…Melanoma, derived from epidermal melanocytes, represents the most serious type of skin cancer and accounts for 80% of skin cancer-related deaths (1). Cul1, an essential scaffold of the SCF (Skp1/Cullin/Rbx1/F-box protein) E3 ubiquitin ligase complex, has been reported to be overexpressed in many cancer tissues and is significantly correlated with the poor prognosis of tumors, including hepatocellular carcinoma, colorectal cancer, glioma, lung cancer, breast cancer and gastric cancer (2)(3)(4)(5)(6)(7). In melanoma, Cul1 expression is increased in the early stages of melanoma (8).…”
Section: Introductionmentioning
confidence: 99%